2020
DOI: 10.1101/2020.07.14.20151126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection induces robust, neutralizing antibody responses that are stable for at least three months

Abstract: SARS-CoV-2 has caused a global pandemic with millions infected and numerous fatalities. Questions regarding the robustness, functionality and longevity of the antibody response to the virus remain unanswered. Here we report that the vast majority of infected individuals with mild-to-moderate COVID-19 experience robust IgG antibody responses against the viral spike protein, based on a dataset of 19,860 individuals screened at Mount Sinai Health System in New York City. We also show that titers are stable for at… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
140
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(173 citation statements)
references
References 32 publications
32
140
0
1
Order By: Relevance
“…The neutralization titers induced by immunization with of 1 µg of vaccine with R-DOTAP (ID 50 of ~476) and 5 µg of vaccine with AddaVax groups (ID 50 of ~515) appeared to be the highest and were comparable to each other. These titer levels are also in the higher range of human convalescent serum neutralization titers as measured in our previous studies (19,23). Interestingly, although the group receiving 5 µg of vaccine with R-DOTAP developed the most abundant binding antibodies detected by ELISA, these sera were not the most neutralizing ones suggesting R-DOTAP might have a different impact on immunogenicity compared to AddaVax.…”
Section: The Spike Protein Expressed On Ndv Virions Is Stable In Allasupporting
confidence: 56%
“…The neutralization titers induced by immunization with of 1 µg of vaccine with R-DOTAP (ID 50 of ~476) and 5 µg of vaccine with AddaVax groups (ID 50 of ~515) appeared to be the highest and were comparable to each other. These titer levels are also in the higher range of human convalescent serum neutralization titers as measured in our previous studies (19,23). Interestingly, although the group receiving 5 µg of vaccine with R-DOTAP developed the most abundant binding antibodies detected by ELISA, these sera were not the most neutralizing ones suggesting R-DOTAP might have a different impact on immunogenicity compared to AddaVax.…”
Section: The Spike Protein Expressed On Ndv Virions Is Stable In Allasupporting
confidence: 56%
“…It can be readily incorporated into existing testing platforms and may be of particular value in the selection of donors for convalescent plasma therapy and as a means of monitoring the immune response to vaccination. Given that neutralizing antibody titres have recently been shown to wane fairly rapidly in some (12)(13)(14)20) but not all (15,20) studies, the assay may also be useful for broad serosurveillance, especially as it should be more scalable than the approaches requiring viral infection assays. When coupled with epidemiological studies, it might also be used to assess the risk of infection/re-infection.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA-based profiling has been developed by multiple groups and used to measure the kinetics of the antibody response in patient cohorts following SARS-CoV-2 infection. In several recent studies, including ours, this has revealed the relative stability in the IgG response to the spike and RBD over several months, and a more transient IgM and IgA response that wanes as patients convalesce (11)(12)(13)(14)(15). However, the levels of neutralizing antibodies are not typically measured in large cohorts over time [with a few notable exceptions, e.g.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…These observations are in line with previously published studies and may suggest that those infected do not produce efficient neutralizing antibodies or neutralizing antibodies rapidly wane by the time samples are collected 16,27,28,29 . Detailed longitudinal studies are beginning to emerge, showing that serum antibody levels are relatively stable or decrease over time [30][31][32] . In-line with our results these studies find a positive correlation between IgG titers and neutralization 31,32 .…”
Section: Discussionmentioning
confidence: 99%